The Southern Suburb of Tauric Chersonesos - Solovyova, Natalia; Vakhoneev, Viktor; Pokrovskaya, Anna; Nizov, Yan (Hyperboreus, 2024)
Large-scale archaeological studies were conducted from 2021 to 2023 on the territory of the Southern Suburb of Tauric Chersonesos. The territory is adjacent to the areas of Chersonesos’ necropolis and ancient household development near the defensive walls of the city site. As recently as the first half of the fourth century BC, the territory in front of the city gates was granted a special status. A sacred area with a heroon was established there. One of the earliest of Chersonesos’ religious buildings, the temple in antis of the first half of the fourth century BC, was discovered near the heroon. In the first centuries AD, the Southern Suburb of Chersonesos had already become the formed necropolis. The unique monumental burial buildings were situated close to the city gates. They were placed on the eastern side of the ancient street that went from Chersonesos’ gates through the territory of the city necropolis. Among them there were burial complexes of the second century AD, unique for the northern Black Sea coastal region: a tholos containing a stone sarcophagus with a lead funerary urn, a columbarium for the members of one noble family made of massive, profiled slabs with multiple grave stelae, inscriptions and anthropomorphs, and slab tombs. The burial complex also included the exedra crypt with stone benches and four burial chambers. The extent of archaeological research in the Southern Suburbs of Chersonesos is also evidenced by the collection of archaeological finds from 2021–2023: 6 290 696 artefacts, including an assemblage of amphorae from various Mediterranean and Black Sea coastal region centers of production, coins, lapidary inscriptions, ceramic stamps, terracotta statuettes, many pieces of jewelry made of precious metals, and other groups of artefacts.